The Influence of Per-hectare Premiums on Prices for Rented Agricultural Area and on Agricultural Land Prices - Clemens Fuchs (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2002)
Within the framework of decreasing support for agricultural incomes by market measures, the per-hectare premiums (ha-premiums) clearly have the task and the effect to stabilise farm incomes. Before direct aids were introduced, there had been periods with decreasing prices for agricultural land and for rented agricultural area in real terms, according to the Farm Accountancy Data Network (FADN) data base (specialised crop farms in 53 regions for 11 years) and EUROSTAT data (B, DK, D-W, F, NL in the period 1975 to 1999).Regression analysis is used to show the relationship between ha-premiums, land rental prices and other relevant economic variables, such as land prices, rental share, livestock density, the price index of agricultural products and farm income. The analysis shows increasing price effects due to the introduction of ha-premiums on prices for agricultural land and on rental prices. Landlords received a share of about 6 % to 18 % of the ha-premiums (depending on the data source). An in-sample simulation, 1999-continuation scenario, and scenarios of further CAP (Common Agricultural Policy) reforms are used for the assessment of the ex-post and ex-ante developments. The ongoing reforms of the CAP (Agenda 2000, Mid-term Review) and EU enlargement certainly have implications for the land markets.
Keywords: 330; Agrarboden; Miete; Bodenpreis; Agrarsubvention; Agrareinkommen; EU-Staaten